Negative electrode sheet, method for manufacturing the same, and battery
Patent Information
- Application Number
- CN202611075825.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-23
AI Technical Summary
在液态电解液体系中,钾金属负极面具有以下缺点:第一,枝晶生长,钾离子半径为1.38 Å,远大于锂离子的半径0.76 Å,沉积动力学更差,极易形成树枝状结晶,刺穿隔膜导致短路;第二,界面副反应,钾金属活性远高于锂,与有机电解液持续剧烈反应,消耗电解液和活性钾,形成不稳定、不均匀的固体电解质界面;第三,体积变化与死钾,充放电过程中钾的反复沉积与溶解导致高达300%的体积变化,使SEI膜破裂重组,产生大量与集流体失去电接触的孤立死钾,导致容量迅速衰减和库仑效率低下
[0015]本申请提供的负极极片及其制备方法、电池,通过设置辅助层,在靠近集流体的第一区域设置第一类辅助颗粒,在碳网络内侧构建高亲钾、高导电成核基底,可降低界面能,引导钾离子在集流体表面均匀成核,抑制枝晶生长;
Smart Images

Figure CN122968243A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology, specifically relating to negative electrode sheets and their preparation methods, and batteries. Background Technology
[0002] Metal batteries have broad application prospects in large-scale energy storage due to the abundance of potassium resources, low cost, and high ionic conductivity. However, their commercial application has long been severely constrained by the potassium anode problem. In liquid electrolyte systems, the potassium metal anode surface has the following disadvantages: First, dendrite growth. The radius of potassium ions is 1.38 Å, much larger than that of lithium ions (0.76 Å), resulting in poorer deposition kinetics and a high tendency to form dendritic crystals that can puncture the separator and cause short circuits. Second, interfacial side reactions. Potassium metal is much more reactive than lithium, reacting violently and continuously with organic electrolytes, consuming electrolyte and active potassium, forming an unstable and uneven solid electrolyte interface. Third, volume changes and dead potassium. Repeated deposition and dissolution of potassium during charging and discharging lead to volume changes of up to 300%, causing the SEI film to rupture and reorganize, producing a large amount of isolated dead potassium that has lost electrical contact with the current collector, resulting in rapid capacity decay and low coulombic efficiency.
[0003] Current lithium-based technologies generally adopt the scheme of physically mixing Ag with auxiliary metals and randomly dispersing them in carbon materials, but this is completely unsuitable for potassium systems and has the following defects: (1) Ag and metal interface contact is unstable, and potassium is easily separated during deposition, losing the synergistic potassium affinity effect; (2) Metal particles are easy to migrate and agglomerate, inducing local high current density, leading to rampant potassium dendrite growth; (3) Metal is directly exposed to electrolyte, and violent side reactions occur with highly active potassium, resulting in continuous dissolution, causing activity loss and cycle decay.
[0004] Therefore, the structural design of potassium metal batteries still faces problems such as lack of interface control, dendrite growth, and lack of stable anchoring mechanism. Summary of the Invention
[0005] In view of this, the first aspect of this application provides a negative electrode sheet, the negative electrode sheet including a current collector and an auxiliary layer disposed on the current collector, the auxiliary layer including a carbon material, a first type of auxiliary particles and a second type of auxiliary particles; the auxiliary layer includes a first region close to the current collector and a second region away from the current collector, the first type of auxiliary particles being disposed in the first region and the second type of auxiliary particles being disposed in the second region; The first type of auxiliary particle includes a silver core and a first metal layer covering the silver core, wherein the material of the first metal layer is selected from at least one of zinc, magnesium, and indium; The second type of auxiliary particle includes a silver core and a second metal layer covering the silver core, wherein the material of the second metal layer is selected from at least one of tin, antimony, and bismuth.
[0006] The particle size of the first type of auxiliary particles is 50nm~100nm; And / or, the particle size of the second type of auxiliary particles is 100nm~150nm; And / or, the thickness of the first metal layer is 5nm~10nm; And / or, the thickness of the second metal layer is 10nm~15nm; And / or, the thickness of the auxiliary layer is 5μm~50μm; And / or, the total mass ratio of the silver core, the first metal layer and the second metal layer to the mass ratio of the carbon material is (0.2-5):1.
[0007] The carbon material is a nitrogen-doped porous carbon material, which is selected from at least one of nitrogen-doped mesoporous carbon, nitrogen-doped carbon nanofibers, and nitrogen-doped reduced graphene oxide. The carbon material forms a nitrogen-doped carbon network with a pore size of 50 nm to 300 nm and a porosity of 60% to 85%.
[0008] The nitrogen doping concentration of the carbon material in the first region is 5% to 10%, and the nitrogen doping concentration of the carbon material in the second region is 1% to 5%.
[0009] The carbon material forms a carbon network, and the first type of auxiliary particles are disposed on the side of the carbon network close to the current collector, with the spacing between two adjacent first type of auxiliary particles being 30nm~60nm. The second type of auxiliary particles are disposed on the side of the carbon network away from the current collector, and the spacing between two adjacent second type of auxiliary particles is 60nm~100nm.
[0010] The auxiliary layer further includes a potassium salt, the potassium salt being selected from at least one of potassium fluoride and potassium nitrate.
[0011] The potassium salt accounts for 0.1% to 5% of the total mass of the auxiliary layer. And / or, the distance between the surface of the first type of auxiliary particles and the surface of the potassium salt nanocrystal cluster is 20 nm to 50 nm; And / or, the distance between the surface of the second type of auxiliary particles and the surface of the potassium salt nanocrystal cluster is 50 nm to 100 nm.
[0012] A second aspect of this application provides a method for preparing a negative electrode sheet, the method comprising: Provide current collectors; Carbon material, first type of auxiliary particles, and binder are mixed and dispersed in a solvent to obtain a first slurry; carbon material, second type of auxiliary particles, and binder are mixed and dispersed in a solvent to obtain a second slurry; wherein, the first type of auxiliary particles includes a silver core and a first metal layer covering the silver core, the material of the first metal layer being selected from at least one of zinc, magnesium, and indium; the second type of auxiliary particles includes a silver core and a second metal layer covering the silver core, the material of the second metal layer being selected from at least one of tin, antimony, and bismuth; The first slurry and the second slurry are coated onto the current collector to obtain the negative electrode sheet as provided in the first aspect of this application.
[0013] A third aspect of this application provides a battery comprising a negative electrode, a positive electrode, an electrolyte, and a separator as provided in the first aspect of this application.
[0014] The electrolyte includes an auxiliary agent, and the material of the auxiliary agent is selected from at least one of fluoroethylene carbonate and potassium nitrate.
[0015] The negative electrode sheet and its preparation method and battery provided in this application, by setting an auxiliary layer, set a first type of auxiliary particles in the first region near the current collector, and construct a highly potassium-loving and highly conductive nucleation substrate inside the carbon network, can reduce the interface energy, guide potassium ions to uniformly nucleate on the surface of the current collector, and inhibit dendrite growth. Furthermore, in the second region far from the current collector, a second type of auxiliary particles are set. Tin, antimony, and bismuth can form an alloy phase with potassium, build a stable corrosion-resistant interface on the outside of the carbon network, delay the side reaction between the electrolyte and potassium, and also serve as a three-dimensional framework to buffer the volume expansion of potassium during deposition and dissolution, so as to prevent the SEI film from rupturing. At the same time, the first type of auxiliary particles and the second type of auxiliary particles are set in separate areas to avoid mutual interference between the first type of auxiliary particles and the second type of auxiliary particles; Furthermore, both the first and second types of auxiliary particles use different types of metals to encapsulate the silver core, which not only enables regional functional regulation but also protects the silver core and achieves interface stability. In addition, the carbon material forms a carbon network, and the three-dimensional pore structure can accommodate the deposited potassium, buffer volume changes, and provide a huge specific surface area to reduce local current density. Therefore, the negative electrode provided in this application can be adapted to potassium metal batteries, realizing the construction of a potassium-loving, stable and ion-conducting auxiliary layer in a liquid environment, and achieving highly reversible deposition and dissolution of potassium. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the embodiments of this application will be described below.
[0017] Figure 1This is a schematic diagram of the structure of the negative electrode sheet provided in one embodiment of this application.
[0018] Figure 2 This is a schematic diagram of the structure of a first type of auxiliary particle provided in an embodiment of this application.
[0019] Figure 3 This is a schematic diagram of the structure of the second type of auxiliary particles provided in one embodiment of this application.
[0020] Figure 4 This is a schematic flowchart illustrating a method for preparing a negative electrode sheet according to an embodiment of this application.
[0021] Figure 5 The battery test diagrams are obtained from the negative electrode sheets in Examples 1-2 and Comparative Examples 1-5.
[0022] Labeling: negative electrode 1, current collector 10, auxiliary layer 20, carbon network 21, first type of auxiliary particle 22, first metal layer 221, second type of auxiliary particle 23, second metal layer 231, silver core 24, first region 25, second region 26. Detailed Implementation
[0023] The following are preferred embodiments of this application. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of this application, and these improvements and modifications are also considered to be within the scope of protection of this application.
[0024] In view of this, in order to solve the above problems, please refer to the following: Figures 1-3 This embodiment provides a negative electrode sheet 1, which includes a current collector 10 and an auxiliary layer 20 disposed on the current collector 10. The auxiliary layer 20 includes a carbon material, a first type of auxiliary particles 22 and a second type of auxiliary particles 23. The auxiliary layer 20 includes a first region 25 close to the current collector 10 and a second region 26 away from the current collector 10. The first type of auxiliary particles 22 are disposed in the first region 25 and the second type of auxiliary particles 23 are disposed in the second region 26.
[0025] The first type of auxiliary particle 22 includes a silver core 24 and a first metal layer 221 covering the silver core 24. The material of the first metal layer 221 is selected from at least one of zinc, magnesium, and indium.
[0026] The second type of auxiliary particle 23 includes a silver core 24 and a second metal layer 231 covering the silver core 24. The material of the second metal layer 231 is selected from at least one of tin, antimony, and bismuth.
[0027] The negative electrode 1 is where potassium metal is deposited and dissolved in the battery. It is the electrochemical reaction interface where potassium ions are reduced to metallic potassium and metallic potassium is oxidized to potassium ions, thus realizing discharge and electrochemical reaction.
[0028] The current collector 10 is a key component connecting the electrode active material to the external circuit. The current collector 10 is used to collect and conduct current, and also to support the electrode structure.
[0029] The auxiliary layer 20 typically employs a combination of carbon materials, first-type auxiliary particles 22, and second-type auxiliary particles 23 to construct a potassium-loving, stable, and ion-conducting auxiliary layer 20 in a liquid environment, thereby achieving highly reversible deposition and dissolution of potassium.
[0030] Specifically, both the first type of auxiliary particles 22 and the second type of auxiliary particles 23 use different types of metals to encapsulate the silver core 24, which not only enables regional functional regulation but also protects the silver core 24 and achieves interface stability.
[0031] First, silver itself has extremely high electronic conductivity and chemical stability, so silver nucleus 24 provides a fast electron transport channel as the core, reducing local current density; in addition, silver does not form an alloy with potassium, which can prevent silver nucleus 24 from undergoing volume changes and cracking during cycling.
[0032] Secondly, the outer layer of the silver core 24 is covered with a metal layer, which can prevent the silver core 24 from being directly exposed to the electrolyte and prevent silver ions from dissolving. Also, the different first metal layers 221 and second metal layers 231 have different functions.
[0033] For the first type of auxiliary particles 22, a first metal layer 221 made of zinc, and / or magnesium, and / or indium coats the silver core 24. Zinc, magnesium, and indium have a strong affinity for potassium, which can guide potassium ions to nucleate uniformly on the surface of the current collector 10 and inhibit dendrite growth.
[0034] For the second type of auxiliary particles 23, a second metal layer 231 prepared of tin, and / or antimony, and / or bismuth covers the silver core 24. Tin, antimony, and bismuth can form alloy phases with potassium, such as K4Sn, K3Sb, K3Bi, etc., to provide reversible potassium storage capacity and can also serve as a three-dimensional framework to buffer the volume expansion of potassium during deposition and dissolution, so as to prevent the SEI film from rupturing.
[0035] Furthermore, the first type of auxiliary particles 22 and the second type of auxiliary particles 23 are arranged in partitions in the auxiliary layer 20. The first type of auxiliary particles 22, which have a high affinity for potassium, are located in the first region 25 near the current collector 10, and can preferentially induce potassium to spread and nucleate in two dimensions on the surface of the current collector 10, avoiding top growth and dendrite piercing of the membrane caused by random nucleation of potassium on the surface of the auxiliary layer 20.
[0036] The second type of auxiliary particles 23, which can form an alloy phase, are located in the second region 26 far from the current collector 10. They can provide three-dimensional skeleton support in the later stage of potassium deposition, absorb excess potassium metal, limit the thickness of the deposited layer, and buffer volume changes through alloying reaction.
[0037] The carbon material forms a carbon network 21, and the three-dimensional porous structure can accommodate deposited potassium, buffer volume changes, and provide a huge specific surface area to reduce local current density.
[0038] Optionally, the molar ratio of the first metal layer 221 material to the second metal layer 231 material is (1~9):(9~1).
[0039] The molar ratio of the first metal layer 221 material to the second metal layer 231 material can be exemplified as 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, or 9:1, etc.
[0040] Preferably, the molar ratio of the first metal layer 221 material to the second metal layer 231 material is (3~4):1.
[0041] This embodiment limits the molar ratio of the first metal layer 221 material to the second metal layer 231 material to (3~4):1, with potassium-loving nucleation as the dominant design. The auxiliary layer 20 is more inclined to promote the uniform nucleation and rapid deposition kinetics of potassium metal, and the buffer function of alloying serves as an auxiliary support.
[0042] Preferably, the molar ratio of the first metal layer 221 material to the second metal layer 231 material is 1:(2~3).
[0043] This embodiment limits the molar ratio of the first metal layer 221 material to the second metal layer 231 material to 1:(2~3), with alloying buffering as the main design, and the auxiliary layer 20 is more inclined to high areal capacity potassium storage and volume expansion buffering, with potassium-loving nucleation function as an auxiliary support.
[0044] Optionally, in the first type of auxiliary particles 22, the molar ratio of silver to the first metal layer 221 material is (1~99):1.
[0045] In the first type of auxiliary particles 22, the molar ratio of silver to the first metal layer 221 material can be exemplified as 1:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, or 99:1, etc.
[0046] Preferably, in the first type of auxiliary particles 22, the molar ratio of silver to the first metal layer 221 material is (1~20):1.
[0047] This embodiment limits the molar ratio of silver to the first metal layer 221 material to (1~20):1, which not only enables the first metal layer 221 to provide strong potassium-affinity nucleation and deposition functions, but also ensures that the electron conduction network between particles is not interrupted, so as to take into account both the potassium-affinity function and the conductivity function of the first type of auxiliary particles 22.
[0048] Optionally, in the second type of auxiliary particles 23, the molar ratio of silver to the second metal layer 231 material is (1~99):1.
[0049] In the second type of auxiliary particles 23, the molar ratio of silver to the second metal layer 231 material can be exemplified as 1:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, or 99:1, etc.
[0050] Preferably, in the second type of auxiliary particles 23, the molar ratio of silver to the second metal layer 231 material is (5~30):1.
[0051] This embodiment limits the molar ratio of silver to the second metal layer 231 material to (5~30):1, which not only enables the second metal layer 231 to provide the functions of alloying reaction and suppressing volume expansion, but also ensures that the electron conduction network between particles is not interrupted, so as to take into account the alloying reaction and suppressing volume expansion functions of the second type of auxiliary particles 23.
[0052] In summary, the negative electrode 1 provided in this embodiment, by setting an auxiliary layer 20 and setting first-type auxiliary particles 22 in the first region 25 near the current collector 10, constructs a highly potassium-loving and highly conductive nucleation substrate inside the carbon network 21, which can reduce the interface energy, guide potassium ions to uniformly nucleate on the surface of the current collector 10, and suppress dendrite growth.
[0053] Furthermore, a second type of auxiliary particles 23 are set in the second region 26 away from the current collector 10. Tin, antimony, and bismuth can form an alloy phase with potassium to build a stable corrosion-resistant interface on the outside of the carbon network 21, and delay the side reaction between the electrolyte and potassium. They can also serve as a three-dimensional framework to buffer the volume expansion of potassium during the deposition and dissolution process, so as to prevent the SEI film from rupturing.
[0054] Meanwhile, by separating the first type of auxiliary particles 22 and the second type of auxiliary particles 23, interference between the first type of auxiliary particles 22 and the second type of auxiliary particles 23 is avoided.
[0055] Therefore, the negative electrode 1 provided in this embodiment can be adapted to potassium metal batteries, realizing the construction of a potassium-loving, stable and ion-conducting auxiliary layer 20 in a liquid environment, and achieving highly reversible deposition and dissolution of potassium.
[0056] Optionally, the particle size of the first type of auxiliary particles 22 is smaller than the particle size of the second type of auxiliary particles 23.
[0057] In one embodiment, the particle size of the first type of auxiliary particles 22 is 50 nm to 100 nm.
[0058] The particle size of the first type of auxiliary particles 22 can be specifically exemplified as 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, or 100nm, etc.
[0059] If the particle size of the first type of auxiliary particles 22 is less than 50 nm, the particles are prone to agglomeration, which leads to local electric field concentration, easily induces dendrite growth, and the specific surface area is too large, which intensifies the side reaction with the electrolyte and consumes active potassium.
[0060] If the particle size of the first type of auxiliary particles 22 is greater than 100 nm, the specific surface area is insufficient, the density of nucleation sites decreases, the potassium deposition overpotential increases, and dendrites tend to grow rapidly at a few sites. If the particle spacing is too large, a continuous potassium-loving network cannot be formed.
[0061] Therefore, by limiting the particle size of the first type of auxiliary particles 22 to 50nm~100nm, this embodiment can both make the surface electric field of the first type of auxiliary particles 22 uniformly distributed and reduce the local current density, and maintain a high specific surface area to provide sufficient potassium-loving nucleation sites.
[0062] And / or, the particle size of the second type of auxiliary particles 23 is 100nm~150nm.
[0063] The particle size of the second type of auxiliary particles 23 can be specifically exemplified as 100nm, 105nm, 110nm, 115nm, 120nm, 125nm, 130nm, 135nm, 140nm, 145nm, or 150nm, etc.
[0064] If the particle size of the second type of auxiliary particles 23 is less than 100 nm, the particle size is too small and cannot play a supporting role in the skeleton. Moreover, the specific surface area is too high, which can easily aggravate the side reactions.
[0065] If the particle size of the second type of auxiliary particles 23 is greater than 150 nm, the gaps between the second type of auxiliary particles 23 are too large, which cannot effectively support the upper layer of deposited potassium, resulting in a loose and porous deposition layer and a reduction in volumetric energy density.
[0066] Therefore, this embodiment limits the particle size of the second type of auxiliary particles 23 to 100nm~150nm, controls the second type of auxiliary particles 23 to have a larger particle size, so as to provide a larger alloying reaction space, accommodate the volume expansion during potassium metal insertion and extraction, and form a size gradient with the first type of particles to construct a hierarchical pore structure and optimize the electrolyte wetting effect.
[0067] Optionally, the thickness of the first metal layer 221 is less than the thickness of the second metal layer 231.
[0068] And / or, the thickness of the first metal layer 221 is 5nm~10nm.
[0069] The thickness of the first metal layer 221 can be exemplified by 5nm, 6nm, 7nm, 8nm, 9nm, or 10nm, etc.
[0070] If the thickness of the first metal layer 221 is less than 5 nm, it is too thin and the first metal layer 221 is prone to incomplete coverage, resulting in local exposure of the silver nucleus 24, which will come into contact with the electrolyte and cause side reactions. In addition, if the first metal layer 221 with potassium affinity is too thin, the nucleation overpotential will be reduced and the potassium affinity effect will be insufficient.
[0071] If the thickness of the first metal layer 221 is greater than 10 nm, the thickness is too thick, which leads to a decrease in the electronic conductivity of the first type of auxiliary particles 22, an increase in the overall resistance of the first type of auxiliary particles 22, an increase in the local current density, excessive consumption of potassium-loving metal, increased cost, and may trigger unnecessary alloying side reactions.
[0072] Therefore, by limiting the thickness of the first metal layer 221 to 5nm~10nm, this embodiment can not only ensure that the first metal layer 221 completely covers the silver core 24, but also maintain a low potassium ion diffusion resistance and avoid excessively long electron transport paths.
[0073] And / or, the thickness of the second metal layer 231 is 10nm~15nm.
[0074] If the thickness of the second metal layer 231 is less than 10 nm, the thickness is too thin, the alloying capacity is insufficient, it cannot effectively buffer the changes in potassium deposition volume, and the skeleton function is lost.
[0075] If the thickness of the second metal layer 231 is greater than 15nm, the thickness is too thick, which can easily lead to excessive volume expansion stress of the alloyed product, which in turn can easily cause the particle structure to collapse. In addition, the proportion of non-active metal mass is too high, which reduces the overall specific capacity of the electrode.
[0076] Therefore, by limiting the thickness of the second metal layer 231 to 10nm~15nm, this embodiment ensures that the second metal layer 231 has sufficient thickness to accommodate the potassium alloying reaction, while also avoiding excessive stress in the alloying product that could lead to shell cracking.
[0077] And / or, the thickness of the auxiliary layer 20 is 5μm to 50μm.
[0078] The thickness of the auxiliary layer 20 can be exemplified by 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, or 50μm, etc.
[0079] If the thickness of the auxiliary layer 20 is less than 5 μm, the potassium storage space will be insufficient, and potassium metal deposition will easily exceed the thickness of the auxiliary layer 20, forming uncontrolled top dendrites. In addition, the mechanical strength of the auxiliary layer 20 is insufficient, and it cannot suppress volume changes.
[0080] If the thickness of the auxiliary layer 20 is greater than 50 μm, it will result in an excessively long ion transport path, increased concentration polarization, deteriorated rate performance, difficulty in electrolyte wetting, excessively high proportion of inactive materials, and a significant decrease in volumetric energy density.
[0081] Therefore, by limiting the thickness of the auxiliary layer 20 to 5μm~50μm, this embodiment not only provides sufficient potassium storage space, but also avoids the problem of electrolyte drying caused by excessive thickness of the auxiliary layer 20.
[0082] And / or, the total mass ratio of the silver core 24, the first metal layer 221 and the second metal layer 231 to the mass ratio of the carbon material is (0.2-5):1.
[0083] The ratio of the total mass of the silver core 24, the first metal layer 221, and the second metal layer 231 to the mass of the carbon material can be exemplified as 0.2:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, or 5:1, etc.
[0084] If the total mass ratio of the silver core 24, the first metal layer 221, and the second metal layer 231 to the carbon material is less than 0.2:1, then there will be too few auxiliary particles, the spacing between the auxiliary particles will be too large, and a continuous electron conduction network cannot be formed, resulting in an increase in local current density. The potassium affinity and alloying function of the auxiliary layer 20 will be insufficient, and potassium deposition will be uncontrolled.
[0085] If the total mass ratio of the silver core 24, the first metal layer 221, and the second metal layer 231 to the carbon material is greater than 5:1, the carbon network 21 will be overfilled by auxiliary particles, losing its flexible buffering capacity. Furthermore, the auxiliary particles are prone to agglomeration, increasing the brittleness of the electrode and making it prone to cracking during rolling.
[0086] Therefore, this embodiment limits the total mass ratio of the silver core 24, the first metal layer 221 and the second metal layer 231 to the carbon material to (0.2-5):1, which takes into account that the carbon material can provide a high specific surface area and a flexible network, and the auxiliary particles can provide high conductivity and potassium-loving sites, so as to achieve a balance between conductivity, mechanical strength and active material loading.
[0087] In another embodiment, the carbon material is a nitrogen-doped porous carbon material, which is selected from at least one of nitrogen-doped mesoporous carbon, nitrogen-doped carbon nanofibers, and nitrogen-doped reduced graphene oxide.
[0088] The carbon material forms a nitrogen-doped carbon network with a pore size of 50 nm to 300 nm and a porosity of 60% to 85%.
[0089] Nitrogen-doped porous carbon materials have potassium-loving sites that can generate local positive charges, interact with potassium ions, reduce potassium ion adsorption energy, and promote uniform distribution of potassium ions. Furthermore, nitrogen doping enhances electronic conductivity and improves the overall conductivity of the auxiliary layer 20.
[0090] In addition, nitrogen-doped porous carbon materials have stronger wettability to electrolytes, which helps to facilitate the rapid transport of potassium ions.
[0091] The pore sizes of nitrogen-doped carbon networks can be specifically exemplified as 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 220nm, 240nm, 260nm, 280nm, or 300nm, etc.
[0092] If the pore size of the nitrogen-doped carbon network is less than 50 nm, the pore size will be too small to accommodate the first type of auxiliary particles 22 and the second type of auxiliary particles 23. This will cause the first type of auxiliary particles 22 and the second type of auxiliary particles 23 to block the pores of the carbon network 21, and will also lead to a decrease in the diffusion coefficient of potassium ions in the micropores and an increase in concentration polarization.
[0093] If the pore size of the nitrogen-doped carbon network is greater than 300 nm, the pore size will be too large, resulting in insufficient specific surface area of the carbon network 21, reduced density of nitrogen doping sites, weakened potassium affinity, unrestricted potassium metal deposition within the pores, easy formation of large dendrites, and easy collapse of the carbon network 21 during rolling or cycling, leading to a decrease in the structural strength of the auxiliary layer 20. Furthermore, the excessively large pore size of the carbon network 21 will easily cause the first type of auxiliary particles 22 and the second type of auxiliary particles 23 to move freely within the pores, resulting in agglomeration.
[0094] Therefore, by limiting the pore size of the nitrogen-doped carbon network to 50nm~300nm, this embodiment can provide sufficient space to accommodate the first type of auxiliary particles 22, the second type of auxiliary particles 23 and potassium metal deposition, while maintaining the high structural strength of the auxiliary layer 20; and the pore size of the carbon network 21 matches the size of the first type of auxiliary particles 22 and the second type of auxiliary particles 23, so that the first type of auxiliary particles 22 and the second type of auxiliary particles 23 can be stably anchored in the pores and prevent migration and aggregation.
[0095] The porosity of nitrogen-doped carbon networks can be specifically exemplified by 60%, 65%, 70%, 75%, 80%, or 85%, etc.
[0096] If the porosity of the nitrogen-doped carbon network is less than 60%, it will result in insufficient electrolyte storage space, causing the electrolyte to dry out in the later stages of the cycle, and insufficient space for potassium metal deposition, leading to SEI rupture due to volume expansion stress.
[0097] If the porosity of the nitrogen-doped carbon network is greater than 85%, the carbon network 21 will be sparse and have insufficient mechanical strength, which will not be able to support the first type of auxiliary particles 22, the second type of auxiliary particles 23 and the deposited potassium. Furthermore, the electron conduction network will be discontinuous, resulting in an increase in local current density.
[0098] Therefore, by limiting the porosity of the nitrogen-doped carbon network to 60% to 85%, the high porosity carbon network 21 can fully wet the electrolyte, reduce the effective current density, and provide a buffer space for potassium metal deposition, absorbing volume expansion.
[0099] In summary, this embodiment employs nitrogen-doped porous carbon material, which has potassium-loving sites. Furthermore, nitrogen has a higher electronegativity than carbon, enabling it to generate local positive charges and form dipole ion interactions with potassium ions, thereby reducing the potassium ion adsorption energy and promoting the uniform distribution of potassium ions.
[0100] In addition, nitrogen-doped porous carbon materials can enhance electronic conductivity and improve the overall conductivity of the auxiliary layer 20.
[0101] Furthermore, the nitrogen doping concentration of the carbon material in the first region 25 is 5% to 10%, and the nitrogen doping concentration of the carbon material in the second region 26 is 1% to 5%.
[0102] For example, the nitrogen doping concentration of the carbon material in the first region 25 can be 5%, 6%, 7%, 8%, 9%, or 10%.
[0103] If the nitrogen doping concentration of the carbon material in the first region 25 is less than 5%, the potassium-loving sites in the first region 25 will be insufficient, and potassium ions will not be able to be effectively guided to migrate to the current collector 10. Potassium will randomly nucleate in the auxiliary layer 20, increasing the risk of dendrite growth.
[0104] If the nitrogen doping concentration of the carbon material in the first region 25 is greater than 10%, it will lead to an increase in the carbon framework defect density in the first region 25, a decrease in electronic conductivity, and excessive potassium affinity, resulting in excessive accumulation of potassium ions in the first region 25, local deposition is too fast, and the formation of a dense potassium layer will hinder subsequent ion transport.
[0105] Therefore, by limiting the nitrogen doping concentration of the carbon material in the first region 25 to 5%~10%, this embodiment not only makes the first region 25 have a strong affinity for potassium, which can guide potassium ions to migrate preferentially to the current collector 10 side to achieve bottom deposition, but also avoids potassium from randomly nucleating on the electrode surface.
[0106] For example, the nitrogen doping concentration of the carbon material in the second region 26 can be 1%, 2%, 3%, 4%, or 5%.
[0107] If the nitrogen doping concentration of the carbon material in the second region 26 is less than 1%, the potassium affinity of the second region 26 will be too weak, the potassium ion transport resistance in the second region 26 will be large, the concentration polarization will be significant, resulting in poor bonding between the SEI film and the carbon network 21, and easy peeling.
[0108] If the nitrogen doping concentration of the carbon material in the second region 26 is greater than 5%, it will result in an excessively strong potassium affinity in the second region 26. Potassium ions will preferentially nucleate in the second region 26, leading to a top growth mode where dendrites grow towards the membrane. Furthermore, high nitrogen doping catalyzes electrolyte decomposition, causing the SEI to continuously thicken and the impedance to increase.
[0109] Therefore, by limiting the nitrogen doping concentration of the carbon material in the second region 26 to 1% to 5%, this embodiment enables the second region 26 to have suitable potassium affinity, which can prevent potassium ions from being excessively retained in the second region 26, promote the diffusion of potassium ions to the first region 25, form a directional concentration gradient, and optimize the ion transport path.
[0110] Optionally, the nitrogen doping concentration of the carbon material in the first region 25 is greater than the nitrogen doping concentration of the carbon material in the second region 26.
[0111] The first type of auxiliary particles 22 are arranged in the first region 25. The nitrogen-doped porous carbon material is covalently bonded to the first type of auxiliary particles 22 and closely anchored to the inner nodes of the carbon network 21, providing a highly conductive channel and inhibiting particle migration and aggregation. The second type of auxiliary particles 23 are arranged in the second region 26. The nitrogen-doped porous carbon material is covalently bonded to the second type of auxiliary particles 23 and loosely anchored to the outer nodes of the carbon network 21. This balances electrolyte wettability and structural stability. By limiting the differential design of the arrangement spacing between the first type of auxiliary particles 22 and the second type of auxiliary particles 23, it can resist the 300% volume expansion of potassium deposition, so as to make the current distribution uniform.
[0112] In another embodiment, the carbon material forms a carbon network 21, and the first type of auxiliary particles 22 are disposed on the side of the carbon network 21 close to the current collector 10, with the spacing between two adjacent first type of auxiliary particles 22 being 30 nm to 60 nm.
[0113] The second type of auxiliary particles 23 are disposed on the side of the carbon network 21 away from the current collector 10, and the spacing between two adjacent second type of auxiliary particles 23 is 60nm~100nm.
[0114] The spacing between two adjacent first-class auxiliary particles 22 refers to the vertical distance between the outer surfaces of two adjacent first-class auxiliary particles 22.
[0115] Optionally, the spacing between two adjacent first-class auxiliary particles 22 is smaller than the particle size of the first-class auxiliary particles 22.
[0116] The spacing between two adjacent first-class auxiliary particles 22 can be specifically exemplified as 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, or 60nm, etc.
[0117] This embodiment limits the spacing between two adjacent first-type auxiliary particles 22 to 30nm~60nm. The electric fields of the adjacent particles are superimposed, guiding potassium metal to be deposited uniformly in the gaps, achieving interparticle filling rather than particle stacking, thereby reducing the overall resistance and improving the overall conductivity of the auxiliary layer 20.
[0118] The spacing between two adjacent second-class auxiliary particles 23 refers to the vertical distance between the outer surfaces of two adjacent second-class auxiliary particles 23.
[0119] The spacing between two adjacent second-class auxiliary particles 23 can be specifically exemplified as 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, or 100nm, etc.
[0120] This embodiment limits the spacing between two adjacent second-type auxiliary particles 23 to 60nm~100nm, which reserves expansion space for the alloying reaction, avoids the second-type auxiliary particles 23 from squeezing each other after expansion and causing structural damage, and can also prevent the alloying products from bridging to form a bulk brittle phase.
[0121] In another embodiment, the auxiliary layer 20 further includes a potassium salt, the potassium salt being selected from at least one of potassium fluoride and potassium nitrate.
[0122] These potassium salts can promote the formation of a robust SEI film rich in highly stable components such as KF and K3N during battery activation, protecting the deposited potassium.
[0123] When the potassium salt material is selected from potassium fluoride, F - It reacts with potassium metal to produce KF, and possibly K2CO3, KOH, etc., forming an SEI film rich in potassium fluoride. Potassium fluoride has extremely high potassium ion conductivity and chemical stability, which can passivate the potassium metal surface and inhibit the continuous reduction and decomposition of the electrolyte.
[0124] Furthermore, potassium fluoride has a lattice constant that matches that of metallic potassium, which can reduce the epitaxial growth stress of potassium under the SEI film.
[0125] When the potassium salt is selected from potassium nitrate, NO 3- K2O, K2O2, and nitrogen-containing organic matter are generated on the surface of potassium metal by reduction, forming a dense and flexible SEI film that effectively blocks electrolyte penetration.
[0126] Furthermore, the potassium salt accounts for 0.1% to 5% of the total mass of the auxiliary layer 20.
[0127] The percentage of potassium salt mass in the total mass of auxiliary layer 20 can be exemplified as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%, etc.
[0128] If the mass of potassium salt accounts for less than 0.1% of the total mass of the auxiliary layer 20, the SEI film-forming material will be insufficient, and a complete passivation layer cannot be formed. The electrolyte will continue to decompose, the self-repair ability will be weakened, and the SEI will break down in the later stages of cycling, resulting in a decrease in capacity.
[0129] If the mass of potassium salt accounts for more than 5% of the total mass of the auxiliary layer 20, it will lead to a decrease in the mechanical strength of the carbon network 21, an excessive amount of SEI film-forming material will make the SEI too thick, the ion transport resistance will increase sharply, and some potassium salt will not participate in film formation and will exist in a crystalline state, blocking the ion channels.
[0130] Therefore, by limiting the percentage of potassium salt mass to 0.1% to 5% of the total mass of the auxiliary layer 20, this embodiment can provide sufficient SEI film-forming material, passivate the potassium metal surface, and inhibit the continuous reduction and decomposition of the electrolyte.
[0131] And / or, the distance between the surface of the first type of auxiliary particle 22 and the surface of the potassium salt nanocrystal cluster is 20nm~50nm.
[0132] The spacing between the surface of the first type of auxiliary particle 22 and the surface of the potassium salt nanocrystal cluster can be exemplified by 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, or 50nm, etc.
[0133] This embodiment limits the spacing between the surface of the first type of auxiliary particles 22 and the surface of the potassium salt nanocrystal cluster to 20nm~50nm, forming a dense potassium ion conductive layer. This allows the potassium salt located near the current collector 10 to participate in the SEI construction, rapidly passivating the surface of the current collector 10 and providing a stable substrate for subsequent potassium deposition.
[0134] And / or, the distance between the surface of the second type of auxiliary particles 23 and the surface of the potassium salt nanocrystal cluster is 50 nm to 100 nm.
[0135] The spacing between the surface of the second type of auxiliary particles 23 and the surface of the potassium salt nanocrystal cluster can be exemplified by 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, or 100nm, etc.
[0136] This embodiment limits the distance between the surface of the second type of auxiliary particles 23 and the surface of the potassium salt nanocrystal cluster to 50nm~100nm, forming a loose ion transport channel. This allows the potassium salt located on the side away from the current collector 10 to replenish the SEI damage during the cycle, achieving SEI self-repair. Furthermore, the larger distance avoids direct contact between the potassium salt and the alloying metal, preventing side reactions. Also, the potassium salt nanocrystal cluster prevents the diffusion of metal atoms from the first metal layer 221 and the second metal layer 231 into the electrolyte, completely suppressing metal dissolution without affecting potassium ion transport.
[0137] In summary, potassium salts are distributed in a differentiated manner in the form of nanocrystal clusters, forming loose ion transport channels; the potassium salt clusters discontinuously cover the particle surface, preventing the diffusion of metal atoms from the first metal layer 221 and the second metal layer 231 into the electrolyte and completely inhibiting metal dissolution, without affecting potassium ion transport.
[0138] Please refer to this as well. Figures 1-4 This application also provides a method for preparing a negative electrode 1, the method comprising: S100 provides current collector 10.
[0139] S200, carbon material, first type of auxiliary particles 22 and binder are mixed and dispersed in a solvent to obtain a first slurry, and carbon material, second type of auxiliary particles 23 and binder are mixed and dispersed in a solvent to obtain a second slurry; wherein, the first type of auxiliary particles 22 includes a silver core 24 and a first metal layer 221 covering the silver core 24, and the material of the first metal layer 221 is selected from at least one of zinc, magnesium and indium; the second type of auxiliary particles 23 includes a silver core 24 and a second metal layer 231 covering the silver core 24, and the material of the second metal layer 231 is selected from at least one of tin, antimony and bismuth.
[0140] S300, the first slurry and the second slurry are coated on the current collector 10 to obtain the negative electrode 1 as provided in this application.
[0141] For example, carbon material, first type auxiliary particles 22 and binder are dispersed in a solvent and centrifuged to form a uniform first slurry; Carbon materials, second-type auxiliary particles 23 and binder are dispersed in a solvent and centrifuged to form a uniform second slurry. The first slurry is applied to at least one side surface of the current collector 10, and the second slurry is applied to the first slurry; After drying, an auxiliary layer 20 is formed, resulting in the negative electrode sheet 1.
[0142] For carbon materials, type I auxiliary particles 22, and type II auxiliary particles 23, please refer to the above description in this application, and will not be repeated here.
[0143] Optionally, the adhesive is selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0144] Optionally, the silver source used to prepare silver core 24 is selected from at least one of silver nanoparticles, silver nitrate, silver oxide, and silver acetylacetone.
[0145] Optionally, the metal source used to prepare the first metal layer 221 is selected from at least one of the corresponding metal nanoparticles, oxides, nitrates, acetates, and chlorides.
[0146] Optionally, the metal source used to prepare the second metal layer 231 is selected from at least one of the corresponding metal nanoparticles, oxides, nitrates, acetates, and chlorides.
[0147] Optionally, the stirring speed of the slurry is 500 rpm to 3000 rpm, and the stirring time is 30 min to 120 min.
[0148] Optionally, the drying process can be carried out in stages: first, pre-drying at 50℃~90℃ for 5min~60min, followed by vacuum drying at 80℃~120℃ for 6h~24h.
[0149] Optionally, carbon materials and binders are mixed and dispersed in a solvent to obtain a third slurry; Then, the first slurry, the third slurry, and the second slurry are sequentially coated onto the current collector 10 to obtain the negative electrode sheet 1 as provided in this application.
[0150] In summary, the method for preparing the negative electrode 1 provided in this application is simple in preparation process and cost controllable, with simple equipment and short process flow, making it suitable for large-scale industrial production.
[0151] By setting an auxiliary layer 20, the negative electrode 1 sets a first type of auxiliary particles 22 in the first region 25 near the current collector 10, and constructs a highly potassium-loving and highly conductive nucleation substrate inside the carbon network 21, which can reduce the interface energy, guide potassium ions to uniformly nucleate on the surface of the current collector 10, and inhibit dendrite growth. Furthermore, a second type of auxiliary particles 23 are set in the second region 26 away from the current collector 10. Tin, antimony, and bismuth can form an alloy phase with potassium, build a stable anti-corrosion interface on the outside of the carbon network 21, delay the side reaction between the electrolyte and potassium, and also serve as a three-dimensional framework to buffer the volume expansion of potassium during the deposition and dissolution process, so as to prevent the SEI film from rupturing. Meanwhile, the first type of auxiliary particles 22 and the second type of auxiliary particles 23 are separated into different areas to avoid mutual interference between the first type of auxiliary particles 22 and the second type of auxiliary particles 23. Furthermore, both the first type of auxiliary particles 22 and the second type of auxiliary particles 23 are coated with different types of metals to not only achieve regional functional regulation, but also protect the silver core 24 and achieve interface stability. In addition, the carbon material forms a carbon network 21, and the three-dimensional pore structure can accommodate the deposited potassium, buffer volume changes, and provide a huge specific surface area to reduce local current density. Therefore, the negative electrode 1 provided in this application can be adapted to potassium metal batteries, realizing the construction of a potassium-loving, stable and ion-conducting auxiliary layer 20 in a liquid environment, and achieving highly reversible deposition and dissolution of potassium.
[0152] This application also provides a battery, which includes a negative electrode, a positive electrode, an electrolyte, and a separator as described above.
[0153] The battery does not contain potassium foil in its initial state.
[0154] The battery provided in this application, by preparing the negative electrode sheet provided above, can be adapted to potassium metal batteries, realizing the construction of a potassium-loving, stable and ion-conducting auxiliary layer in a liquid environment, and achieving highly reversible deposition and dissolution of potassium.
[0155] Furthermore, the electrolyte includes an auxiliary agent, the material of which is selected from at least one of fluoroethylene carbonate and potassium nitrate.
[0156] The potassium salt in the auxiliary layer of the negative electrode and the auxiliary agent in the electrolyte can work together to enable the auxiliary agent in the electrolyte to form a film quickly during the first charge and discharge, and the potassium salt in the auxiliary layer to be replenished and repaired over a long period of time during cycling, thereby achieving dynamic stability of SEI.
[0157] When the auxiliary material is selected from fluoroethylene carbonate, the fluoroethylene carbonate is reduced on the potassium metal surface to generate KF, ROCO2K, and polycarbonate organic compounds, forming a thin and dense SEI. Furthermore, the F produced by the reduction of fluoroethylene carbonate... - In synergy with potassium fluoride in the auxiliary layer, an inorganic SEI inner layer with high fluorine content is constructed to enhance the potassium ion transport rate.
[0158] When the auxiliary agent is selected from potassium nitrate, it forms a concentration gradient with the potassium nitrate in the auxiliary layer, driving NO3... - It migrates towards the negative electrode, continuously replenishing the nitrogen-containing components in the SEI, enhancing the SEI's flexibility, and NO3... - Preferential reduction at the dendrite tip forms a local passivation layer, inhibiting the longitudinal growth of dendrites.
[0159] To make the objectives and advantages of this application clearer, the effects of the current collector of this application will be further explained in detail below with reference to specific embodiments 1-2 and comparative examples 1-6.
[0160] Example 1: A negative electrode sheet was prepared by a slurry coating and drying method; The current collector is a stainless steel current collector with a thickness of 10μm; The first type of auxiliary particle includes a silver core and a first metal layer covering the silver core, wherein the material of the first metal layer is selected from indium; The second type of auxiliary particles includes a silver core and a second metal layer covering the silver core, wherein the material of the second metal layer is selected from bismuth; The carbon material is a nitrogen-doped porous carbon material. The nitrogen doping concentration of the carbon material in the first region is 8%, and the nitrogen doping concentration of the carbon material in the second region is 3%.
[0161] The potassium salt material is selected from potassium fluoride. The mass of potassium salt accounts for 1.5% of the total mass of the auxiliary layer. The distance between the surface of the first type of auxiliary particles and the surface of the potassium salt nanocrystal cluster is 30 nm, and the distance between the surface of the second type of auxiliary particles and the surface of the potassium salt nanocrystal cluster is 70 nm. The total mass ratio of Ag, Zn, In, and Bi to the mass ratio of nitrogen-doped porous carbon material is 1:1; the molar ratio of indium to bismuth is 1:1.
[0162] The specific steps for preparing the first type of auxiliary particles and the second type of auxiliary particles are as follows: Step 1: Silver nitrate, PVP, and ascorbic acid are mixed and reacted at 120℃ for 4 hours to obtain silver cores with a particle size of 60nm for use in the first type of auxiliary particles and silver cores with a particle size of 80nm for use in the second type of auxiliary particles. Step 2: Mix silver cores with a particle size of 60 nm and indium nitrate phase, use ascorbic acid for reduction, react at 90 °C for 3 h, deposit an indium alloy shell of 7 nm, and obtain the first type of auxiliary particles with a particle size of 74 nm. Step 3: Mix silver cores with a particle size of 80 nm and bismuth nitrate phase, reduce with ascorbic acid, react at 90 °C for 3 h, deposit a 12 nm bismuth shell, and obtain second-type auxiliary particles with a particle size of 104 nm.
[0163] Then, according to the mass ratio of Ag, Zn, In, Bi to carbon material, the following materials are weighed: first type of auxiliary particles, second type of auxiliary particles, nitrogen-doped mesoporous carbon, polyvinylidene fluoride (PVDF) binder, 0.3 wt% silane coupling agent, and nano KF crystal clusters. Next, nitrogen-doped mesoporous carbon, type I auxiliary particles, binder, silane coupling agent, and nano KF crystal clusters were mixed and dispersed in N-methylpyrrolidone (NMP) solvent and stirred at 2000 rpm for 60 minutes using a planetary centrifuge to form a uniform first slurry. Nitrogen-doped mesoporous carbon, type II auxiliary particles, binder, silane coupling agent, and nano KF crystal clusters were mixed and dispersed in N-methylpyrrolidone (NMP) solvent and stirred at 2000 rpm for 60 minutes using a planetary centrifuge to form a uniform second slurry. Continuing, the first slurry is applied to the surface of the stainless steel current collector using a scraper, and the second slurry is applied to the first slurry.
[0164] Finally, the coated electrode sheet is dried in stages: first, it is dried in an air environment at 80°C for 30 minutes, and then transferred to a vacuum oven at 100°C for 12 hours to finally obtain the negative electrode sheet with an auxiliary layer thickness of about 15μm.
[0165] Example 2: A negative electrode sheet was prepared by a slurry coating and drying method; The current collector is a stainless steel current collector with a thickness of 10μm; The first type of auxiliary particles includes a silver core and a first metal layer covering the silver core, wherein the material of the first metal layer is selected from magnesium. The second type of auxiliary particles includes a silver core and a second metal layer covering the silver core. The material of the second metal layer is selected from antimony. The carbon material is a nitrogen-doped porous carbon material. The nitrogen doping concentration of the carbon material in the first region is 7%, and the nitrogen doping concentration of the carbon material in the second region is 2%.
[0166] The potassium salt material is selected from potassium fluoride. The potassium salt accounts for 1.2% of the total mass of the auxiliary layer. The distance between the surface of the first type of auxiliary particles and the surface of the potassium salt nanocrystal cluster is 25 nm, and the distance between the surface of the second type of auxiliary particles and the surface of the potassium salt nanocrystal cluster is 65 nm. The total mass ratio of Ag, Zn, In, and Bi to the nitrogen-doped porous carbon material is 0.5:1; the molar ratio of magnesium to antimony is 2:1.
[0167] The specific steps for preparing the first type of auxiliary particles and the second type of auxiliary particles are as follows: Step 1: Prepare silver nuclei with a particle size of 50 nm for use in the first type of auxiliary particles and silver nuclei with a particle size of 70 nm for use in the second type of auxiliary particles. Step 2: Deposit a 6nm magnesium shell to obtain first-type auxiliary particles with a particle size of 56nm; Step 3: Deposit an 11nm bismuth shell to obtain second-type auxiliary particles with a particle size of 81nm.
[0168] Then, weigh out the first type of auxiliary particles, the second type of auxiliary particles, nitrogen-doped mesoporous carbon, polyvinylidene fluoride (PVDF) binder, 0.2 wt% silane coupling agent, and nano KF crystal clusters; Next, nitrogen-doped mesoporous carbon, type I auxiliary particles, binder, silane coupling agent, and nano KF crystal clusters were mixed and dispersed in N-methylpyrrolidone (NMP) solvent and stirred at 2000 rpm for 60 minutes using a planetary centrifuge to form a uniform first slurry. Nitrogen-doped mesoporous carbon, type II auxiliary particles, binder, silane coupling agent, and nano KF crystal clusters were mixed and dispersed in N-methylpyrrolidone (NMP) solvent and stirred at 2000 rpm for 60 minutes using a planetary centrifuge to form a uniform second slurry. Continuing, the first paste is applied to the surface of the stainless steel current collector by screen printing, and the second paste is applied to the first paste.
[0169] Finally, the negative electrode sheet was dried under vacuum at 100°C for 24 hours to obtain the final negative electrode sheet, with an auxiliary layer thickness of approximately 15 μm.
[0170] Comparative Example 1: Pure copper foil negative electrode sheet is used.
[0171] Comparative Example 2: A negative electrode sheet with a pure nitrogen-doped carbon layer was prepared, without type I or type II auxiliary particles.
[0172] A pure carbon anode was prepared using a slurry coating and drying method. The anode sheet consisted of a stainless steel current collector and a nitrogen-doped porous carbon layer disposed on its surface. The specific steps are as follows: First, weigh out nitrogen-doped mesoporous carbon and polyvinylidene fluoride (PVDF) binder; Then, the above solid powders were mixed and dispersed in N-methylpyrrolidone (NMP) solvent, and stirred at 2000 rpm for 60 minutes using a planetary centrifugal mixer to form a uniform slurry; Next, the obtained slurry was coated onto the surface of a stainless steel current collector with a thickness of 10 μm using a doctor blade. Finally, the coated electrode sheet was dried in stages: first, it was dried in an air environment at 80°C for 30 minutes, and then transferred to a vacuum oven at 100°C for 12 hours to finally obtain a negative electrode sheet with a pure nitrogen-doped carbon layer, the thickness of which was about 15 μm.
[0173] Comparative Example 3: A negative electrode sheet with silver particles and a nitrogen-doped carbon layer was prepared, with no metal layer outside the silver particles.
[0174] A negative electrode sheet with silver particles and a nitrogen-doped carbon layer was prepared using the same slurry coating and drying method as in Example 1. The negative electrode sheet includes a stainless steel current collector and a silver particle and nitrogen-doped carbon layer disposed on its surface. The specific steps are as follows: First, weigh out silver nanoparticles, nitrogen-doped mesoporous carbon, and polyvinylidene fluoride (PVDF) binder, wherein the mass ratio of Ag to nitrogen-doped porous carbon material is 1:1.
[0175] Then, the above solid powder is mixed and dispersed in N-methylpyrrolidone (NMP) solvent, and stirred at 2000 rpm for 60 minutes using a planetary centrifugal mixer to form a uniform slurry.
[0176] Next, the obtained slurry was coated onto the surface of a stainless steel current collector with a thickness of 10 μm using a doctor blade.
[0177] Finally, the coated electrode sheet was dried in stages: first, it was dried in an air environment at 80°C for 30 minutes, and then transferred to a vacuum oven at 100°C for 12 hours to finally obtain a negative electrode sheet with silver particles and nitrogen-doped carbon layers, the thickness of which is about 15 μm.
[0178] Comparative Example 4: A negative electrode sheet without a silver core and consisting of metal particles and a nitrogen-doped carbon layer was prepared.
[0179] A negative electrode sheet containing silver-core-free metal particles and a nitrogen-doped carbon layer was prepared using the same slurry coating and drying method as in Example 1. The negative electrode sheet includes a stainless steel current collector and a silver-core-free metal particle and nitrogen-doped carbon layer disposed on its surface. The specific steps are as follows: First, weigh out bismuth nanoparticles, indium nanoparticles, nitrogen-doped mesoporous carbon, and polyvinylidene fluoride (PVDF) binder, wherein the total mass ratio of bismuth and indium to the mass ratio of nitrogen-doped porous carbon material is 1:1, and the molar ratio of bismuth to indium is 1:1.
[0180] Then, the above solid powder is mixed and dispersed in N-methylpyrrolidone (NMP) solvent, and stirred at 2000 rpm for 60 minutes using a planetary centrifugal mixer to form a uniform slurry.
[0181] Next, the obtained slurry was coated onto the surface of a 10 μm thick stainless steel (SUS) current collector using a doctor blade.
[0182] Finally, the coated electrode was dried in stages: first, it was dried in an air environment at 80°C for 30 minutes, and then transferred to a vacuum oven at 100°C for 12 hours to obtain a negative electrode with metal particles without silver cores and a nitrogen-doped carbon layer. The thickness of the metal particles without silver cores and the nitrogen-doped carbon layer was about 15 μm.
[0183] Comparative Example 5: Prepare negative electrode sheets with a metal or carbon mass ratio exceeding (0.2-5):1.
[0184] The negative electrode sheet was prepared using the same process as in Example 1. The total mass ratio of Ag, Zn, In, and Bi to the mass ratio of nitrogen-doped porous carbon material was 8:1. The remaining components, molar ratios, and preparation parameters were completely consistent with those in Example 1.
[0185] Battery assembly and performance testing: The negative electrode sheets prepared in Examples 1, 2, and Comparative Examples 1-5 were used to assemble liquid potassium metal coin cells, as follows: A potassium metal sheet was used as the counter electrode, and glass fiber (GF / D) was used as the battery separator. The electrolyte was a mixture of 1 M KPF6 dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, with 2 wt% of fluoroethylene carbonate (FEC) added.
[0186] The batteries were assembled into CR2032 coin cells in an argon-atmospheric glove box. They were then connected to the Xinwei system for electrical performance testing. Cyclic curves for Examples 1 and 2 and Comparative Examples 1-5 were obtained, as shown below. Figure 5 As shown, from Figure 5 It can be concluded that, at a current density of 1C, both Example 1 and Example 2 exhibit excellent cycle stability: Example 1, after 50 cycles, shows a discharge specific capacity of 492.9 mAh g⁻¹. -1 The concentration gradually decreased to 492.7 mAh g. -1 The decay rate was 0.2 mAh g.-1 The decay rate is almost zero; and, in Example 2, 50 cycles from 352.8 mAh g -1 Reduced to 330.8 mAh g -1 The decay rate was 22 mAh g. -1 The attenuation rate was 6.2%, and both achieved low attenuation and high stability.
[0187] However, Comparative Examples 1-5 all showed significantly inferior performance compared to Examples 1-2. Specifically, Comparative Example 1 exhibited a discharge specific capacity that decreased from 345.2 mAh g⁻¹ after 50 cycles. -1 Dropped to 100 mAh g -1 1. The attenuation reached 254.2 mAh g. -1 The attenuation rate was 71.0%. Comparative Example 2, the specific capacity after 50 discharge cycles increased from 340.5 mAh g⁻¹. -1 Reduced to 76 mAh g -1 The attenuation reached 264.5 mAh g. -1 The attenuation rate was 77.7%. Comparative Example 3: The specific capacity after 50 discharge cycles increased from 348.6 mAh g⁻¹. -1 Reduced to 228 mAh g -1 The attenuation reached 120.6 mAh g. -1 The attenuation rate was 34.5%. Comparative Example 4: The specific capacity after 50 discharge cycles increased from 343.2 mAh g⁻¹. -1 Reduced to 169.7 mAh g -1 The attenuation reached 173.5 mAh g. -1 The attenuation rate is 50.5%; Comparative Example 5: The specific capacity after 50 discharge cycles increased from 350.5 mAh g⁻¹. -1 Reduced to 90.8 mAh g -1 The attenuation reached 259.7 mAh g. -1 The attenuation rate was 74.1%.
[0188] In summary, Examples 1-2 solve the three core problems of potassium system interface instability, particle agglomeration, and metal dissolution by using the negative electrode sheet provided in this application. The negative electrode sheet provided in this application can be adapted to potassium metal batteries, realizing the construction of a potassium-loving, stable, and ion-conducting auxiliary layer in a liquid environment, and achieving highly reversible deposition and dissolution of potassium.
[0189] Unless otherwise stated or in case of conflict, the terms or phrases used in this application shall have the following meanings: In this application, terms such as "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of that feature.
[0190] In this application, "one or more" refers to any one, any two, or any two or more of the listed items. "Several" refers to any two or more.
[0191] In this application, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," and "counterclockwise," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.
[0192] In this application, unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part. They can refer to a mechanical connection or an electrical connection. They can refer to a direct connection or an indirect connection through an intermediate medium, or the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in this application can be understood according to the specific circumstances.
[0193] In this application, the terms "embodiment" and "implementation" mean that a specific feature, structure, or characteristic described in connection with an embodiment can be included in at least one embodiment of this application. The appearance of these phrases in various locations throughout the specification does not necessarily refer to the same embodiment, nor are they independent or alternative embodiments mutually exclusive with other embodiments. Those skilled in the art will understand, explicitly and implicitly, that the embodiments described in this application can be combined with other embodiments. Furthermore, it should be understood that the features, structures, or characteristics described in the various embodiments of this application can be arbitrarily combined to form yet another embodiment that does not depart from the spirit and scope of the technical solution of this application, provided there is no contradiction between them.
[0194] The above description represents some embodiments of this application. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of this application, and these improvements and modifications are also considered to be within the scope of protection of this application.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode includes a current collector and an auxiliary layer disposed on the current collector. The auxiliary layer includes a carbon material, a first type of auxiliary particles, and a second type of auxiliary particles. The auxiliary layer includes a first region close to the current collector and a second region away from the current collector. The first type of auxiliary particles are disposed in the first region, and the second type of auxiliary particles are disposed in the second region. The first type of auxiliary particle includes a silver core and a first metal layer covering the silver core, wherein the material of the first metal layer is selected from at least one of zinc, magnesium, and indium; The second type of auxiliary particle includes a silver core and a second metal layer covering the silver core, wherein the material of the second metal layer is selected from at least one of tin, antimony, and bismuth.
2. The negative electrode sheet as described in claim 1, characterized in that, The particle size of the first type of auxiliary particles is 50nm~100nm; And / or, the particle size of the second type of auxiliary particles is 100nm~150nm; And / or, the thickness of the first metal layer is 5nm~10nm; And / or, the thickness of the second metal layer is 10nm~15nm; And / or, the thickness of the auxiliary layer is 5μm~50μm; And / or, the total mass ratio of the silver core, the first metal layer and the second metal layer to the mass ratio of the carbon material is (0.2-5):
1.
3. The negative electrode sheet as described in claim 1, characterized in that, The carbon material is a nitrogen-doped porous carbon material, which is selected from at least one of nitrogen-doped mesoporous carbon, nitrogen-doped carbon nanofibers, and nitrogen-doped reduced graphene oxide. The carbon material forms a nitrogen-doped carbon network with a pore size of 50 nm to 300 nm and a porosity of 60% to 85%.
4. The negative electrode sheet as described in claim 3, characterized in that, The nitrogen doping concentration of the carbon material in the first region is 5% to 10%, and the nitrogen doping concentration of the carbon material in the second region is 1% to 5%.
5. The negative electrode sheet as described in claim 1, characterized in that, The carbon material forms a carbon network, and the first type of auxiliary particles are disposed on the side of the carbon network close to the current collector, with the spacing between two adjacent first type of auxiliary particles being 30nm~60nm; The second type of auxiliary particles are disposed on the side of the carbon network away from the current collector, and the spacing between two adjacent second type of auxiliary particles is 60nm~100nm.
6. The negative electrode sheet as described in claim 1, characterized in that, The auxiliary layer also includes a potassium salt, the potassium salt being selected from at least one of potassium fluoride and potassium nitrate.
7. The negative electrode sheet as described in claim 6, characterized in that, The potassium salt accounts for 0.1% to 5% of the total mass of the auxiliary layer; And / or, the distance between the surface of the first type of auxiliary particles and the surface of the potassium salt nanocrystal cluster is 20 nm to 50 nm; And / or, the distance between the surface of the second type of auxiliary particles and the surface of the potassium salt nanocrystal cluster is 50 nm to 100 nm.
8. A method for preparing a negative electrode sheet, characterized in that, The method for preparing the negative electrode sheet includes: Provide current collectors; Carbon material, first type of auxiliary particles, and binder are mixed and dispersed in a solvent to obtain a first slurry; carbon material, second type of auxiliary particles, and binder are mixed and dispersed in a solvent to obtain a second slurry; wherein, the first type of auxiliary particles includes a silver core and a first metal layer covering the silver core, the material of the first metal layer being selected from at least one of zinc, magnesium, and indium; the second type of auxiliary particles includes a silver core and a second metal layer covering the silver core, the material of the second metal layer being selected from at least one of tin, antimony, and bismuth; The first slurry and the second slurry are coated onto the current collector to obtain the negative electrode sheet as described in any one of claims 1-7.
9. A battery, characterized in that, The battery includes a negative electrode, a positive electrode, an electrolyte, and a separator as described in any one of claims 1-7.
10. The battery as claimed in claim 9, characterized in that, The electrolyte includes an auxiliary agent, the material of which is selected from at least one of fluoroethylene carbonate and potassium nitrate.